Analysis of Influence Financial Ratios on Sharia Banking Performance in Indonesia (Empirical Study at Bank Muamalat Indonesia, Bank Syariah Mandiri, and Bank Mega Syariah) - Shulhah Nurullaily (Global Review of Islamic Economics and Business, 2016)
This study aims to examine the performance of Sharia Banking in Indonesia after experiencing slowing growth due to the impact of the United States crisis in 2008/2009. Factors used to measure the performance of sharia banking represented by ROA are CAR, NPF, BOPO, NM and FDR. This research uses multiple linear regression analysis with sample of research of Bank Muamalat, Bank Mega Syariah, and Bank Syariah Mandiri with the period of research from the first quarter 2008 to the fourth quarter 2011. The result of this research that is NM and FDR have positive significant effect on ROA, while BOPO has a significant negative effect on ROA, CAR and NPF have no influence on ROA.